Paul Marchand, F.M.C. - Chesnutt, Charles W. (Charles Waddell), 1858-1932 (Princeton legacy library, 1999)
Evoking the atmosphere of early-nineteenth-century New Orleans and the deadly aftermath of the San Domingo slave revolution, this historical novel begins as its protagonist puzzles over the seemingly prophetic dream of an aged black praline seller in the famous Place d'Armes. Paul Marchand, a free man of color living in New Orleans in the 1820s, is despised by white society for being a quadroon, yet he is a proud, wealthy, well-educated man. In this city where great wealth and great poverty exist side by side, the richest Creole in town lies dying. The family of the aged Pierre Beaurepas eage.